DHF Awareness Counseling and the Production of Natural Larvicide "ABATE CELERY" as a Mosquito Larvae Killer - Yulia Irvani Dewi; Aisyah Wati; Ayu Wulandari; Azzahra Jasmine Budiono; Bayong Montella; Desi Qhairani Muraji Zagoto; Farazila Farazila; Jesika Delya Putri; Kurnia Wulandari; Melani Putri; Nabila Naila Rahman; Najwa Kiramy; Riska Aulia Putri (NuCSJo : Nusantara Community Service Journal, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease transmitted by the Aedes aegypti mosquito and remains a public health problem in Indonesia, especially in wetland areas such as Limbungan Baru Village, Rumbai District, Pekanbaru City. Humid environments and stagnant water are ideal breeding grounds for mosquito larvae. This community service activity aims to increase public knowledge about DHF prevention and introduce the production of natural larvicide "Abate Celery" made from celery herb (Apium graveolens L.) as an environmentally friendly alternative to eradicate mosquito larvae. The implementation method includes surveys, counseling, demonstrations, and questions and answers attended by 23 residents representing each RT in RW 06 Limbungan Baru in October 2025. Evaluation was carried out after the counseling through a pre-test and post-test with 10 questions related to DHF and its prevention. The results showed an increase in community knowledge, from a pre-test score of 66.5 to 90.5 in the post-test, indicating the effectiveness of the outreach activities. Furthermore, the community was able to practice making natural larvicides. This activity contributed to raising public awareness of the importance of environmental cleanliness and the use of natural ingredients as a sustainable dengue prevention effort.